Influence of Liquidity on Profitability in PT Indofood Sukses Makmur Tbk - Nurlela Nurlela; Hieronimus Erwin Indrawan; Mahmud Syarif; Yudha Febri Al Paksi; Ananto Krisna Wardhana (Institute of Computer Science (IOCS), 2021)
PT Indofood Sukses Makmur Tbk is a consumer goods industry sector engaged in the production of food and beverage ingredients, with production activities based on policies established by the company. The purpose of this study was to determine the effect of liquidity on profitability at PT Indofood Sukses Makmur Tbk. Types of quantitative descriptive research with data collection methods are observation and documentation studies. The data used is secondary data obtained from the financial statements of PT Indofood Sukses Makmur Tbk and analyzed using correlation coefficient tests, coefficients of determination, simple linear regression equations and processed using IBM SPSS Statistics Version 28.0.0 software. 0.138. The results of the determination test show that there is no significant effect between the Current Ratio and the Ratio On Assets of 0.190. The simple regression equation formed is not significant between the Current Ratio and the Ratio On Asset, namely Y = 4.090-0.853 X.